DOES THE AFRICAN GOLDEN WOLF, Canis anthus, PLAY THE ROLE OF REGULATOR OF NATURAL MICROMAMMAL POPULATIONS IN THE EDOUGH MOUNTAIN RANGE (NORTHEASTERN ALGERIA)? - BELBEL, FATMA; BOUKHEROUFA, MEHDI; SAKRAOUI, RYM; ABDELLI, MOHAMED; BENOTMANE, KAMELIA HESNI; HENNADA, LINA RANIA IKRAM; SAKRAOUI, FERIEL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The objective of this study is to analyse the share of small mammals in the diet of the African Golden Wolf (Canis anthus), to deduce its functional role as regulator of densities of this food category. Methods: Sampling campaign was carried out during the winter period 2020, when trophic resources are least abundant, and when the small mammals are most abundant. We choosed two different ecological conditions to conduct the scats sampling in the Edough Mountain Range, once in the natural environment of Berouaga and the second in Ain Barbar landfill. 30 droppings were collected in the field and at each site, then sterilized, washed, sorted and identified in the laboratory. Results: We were able to identify rodents, wild boar’s carcass, arthropods, birds, plants and wastes (plastic bag, papers, aluminium foils..). Occurrence frequencies analysis of item preys stand shows that the African golden wolf consumes micromammals less frequently in the natural environment, to avoid interspecific competition pressure with other predators like common genets, and does not consume them at all in the anthropized environment, since the anthropogenic resources are abundant, easily accessible and requiring no energy loss. Conclusion: By its opportunistic behavior, the African Golden Wolf turns away from its role as regulator of natural populations of small mammals, in the presence of anthropogenic resources.